Pengaruh Penggunaan Metode Observasi dan Metode Diskusi pada Sifat-Sifat Benda Cair Terhadap Hasil Belajar Siswa Sekolah Dasar - Andi Suhandi; P Patonah (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This study aims to determine whether there are differences in student learning outcomes by using the observation method and the method of discussion on the subject of the concept of the properties of liquid objects in class V of the Estuary 34 / I Muara Bulian SDN. The results of the study and discussion can be concluded that there are differences in student learning outcomes in learning using observation methods and discussion methods on the material properties of liquid class V semester 2 of 34 / I Lotus Elementary School 2014/2015 Academic Year. The results of student evaluation showed that the use of the observation learning method was better than using the discussion method.